Jerky : make your own delicious jerky and jerky dishes using beef, venison, fish, or fowl - Livingston, A. D., 1932- (Lyons Press, 2011)
A guide to making high-protein, low-fat - delicious jerky and jerky dishes using beef, venison, fish, or fowl.